Fanning the flames: political discourse analysis of anti-austerity social movement intervention in the UK general elections of 2015 and 2017 - Rhodes, Abigail (2020)
Once thought of as sitting outside of institutional politics, social movements have been a consistent and dominant feature of the political landscape in the twenty-first century. Social movements, as political actors, can have a refining and reinforcing effect on conventional politics through the highlighting of specific issues that shape both political party and voter behaviour. However, in the field of political communication the literature has traditionally focused on the ways in which institutional political actors – political parties and politicians – have communicated, often via the media, with the electorate. Conversely, the social movement literature has tended to focus on extra-parliamentary politics that occur outside of election time and, as such, neglects this aspect of the political process. This thesis begins to address that lacuna by exploring the role of communication by the UK-based social movement The People’s Assembly Against Austerity in electoral politics and assesses how far they can be seen as political actors in electoral campaigns.